Crustal structure and origin of the Cape Verde Rise - Pim, J; Peirce, C; Watts, A; Grevemeyer, I; Krabbenhoeft, A (2008)
The Cape Verde Islands are located on a mid-plate topographic swell and are thought to have formed above a deep mantle plume. Wide-angle seismic data have been used to determine the crustal and uppermost mantle structure along a ~ 440 km long transect of the archipelago. Modelling shows that 'normal' oceanic crust, ~ 7 km in thickness, exists between the islands and is gently flexed due to volcano loading. There is no direct evidence for high density bodies in the lower crust or for an anomalously low density upper mantle. The observed flexure and free-air gravity anomaly can be explained by volcano loading of a plate with an effective elastic thickness of 30 km and a load and infill density of 2600 kg m- 3. The origin of the Cape Verde swell is poorly understood. An elastic thickness of 30 km is expected for the ~ 125 Ma old oceanic lithosphere beneath the islands, suggesting that the observed height of the swell and the elevated heat flow cannot be attributed to thermal reheating of the lithosphere. The lack of evidence for high densities and velocities in the lower crust and low densities and velocities in the upper mantle, suggests that neither a crustal underplate or a depleted swell root are the cause of the shallower than expected bathymetry and that, instead, the swell is supported by dynamic uplift associated with the underlying plume. © 2008 Elsevier B.V. All rights reserved.